2020
DOI: 10.2196/20691
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of a Virtual Reality Headset Designed for Fall Prevention in Older Adults: Questionnaire Study

Abstract: Background Falls are a common phenomenon among people aged 65 and older and affect older adults’ health, quality of life, and autonomy. Technology-based intervention programs are designed to prevent the occurrence of falls and their effectiveness often surpasses that of more conventional programs. However, to be effective, these programs must first be accepted by seniors. Objective Based on the technology acceptance model, this study aimed to examine th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…Perceived ease of use was the lowest predictor of intention to use, while remaining a significant predictor, indicating that this predictor is relevant for older adults who are not always familiar with technologies [ 27 ] but also that it is not the most important factor for them in terms of MTR acceptance. This pattern of results has been found in several studies conducted with older adults and with other innovative technologies such as virtual reality head-mounted display [ 15 ]. Perceived ease of use was also found in the present study to be the variable with the highest score compared with the mean of the scale.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Perceived ease of use was the lowest predictor of intention to use, while remaining a significant predictor, indicating that this predictor is relevant for older adults who are not always familiar with technologies [ 27 ] but also that it is not the most important factor for them in terms of MTR acceptance. This pattern of results has been found in several studies conducted with older adults and with other innovative technologies such as virtual reality head-mounted display [ 15 ]. Perceived ease of use was also found in the present study to be the variable with the highest score compared with the mean of the scale.…”
Section: Discussionsupporting
confidence: 77%
“…Participants responded to the four items assessing perceived usefulness (e.g., “Using this robot would allow me to do physical activity efficiently” ), the three items assessing perceived ease of use (e.g., “I think it would be easy to learn how to use this robot” ), the three items assessing perceived enjoyment (e.g., “Using this robot would be fun” ), the three items assessing subjective norms (e.g., “The people who are important to me would encourage me to use this robot” ), and the three items assessing intention to use (e.g., “If I had the opportunity to have easy access to this robot, I would like to use it” ) on a Likert scale from 1 ( strongly disagree ) to 5 ( strongly agree ). These items were developed based on items commonly used in the TAM and on other studies specifically investigating technology acceptance by older adults [ 15 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the abovementioned characteristics of VR technology that make it loved by many people and widely used in many fields, such as the medical field. To date, VR has successfully been applied in many clinical settings [ 1 ], such as helping to treat anxiety disorders [ 37 , 38 ], alleviating fear [ 39 ], managing pain [ 33 , 34 , 40 ], supporting physical recovery [ 41 ], and preventing falls in elderly individuals [ 42 ]. Furthermore, an interactive training system for public health emergency preparedness for major emerging infectious diseases based on VR should be established [ 43 ].…”
Section: How Does Vr Technology Work In a Medical Setting?mentioning
confidence: 99%
“…Although exposure to VR application may result in symptoms of motion sickness for some people (e.g., eye fatigue, headaches, and nausea) (Park et al, 2019), its advantages include a secure environment, high ecological validity, and an inexpensive aid to support active aging (Appel et al, 2020;Kim et al, 2021;Syed-Abdul et al, 2019). A previous study revealed the acceptance (or positive perception) of older adults toward using VR (Mascret et al, 2020), namely, they perceived the VR to be useful, an enjoyable experience, and easy to use (Mascret et al, 2020;Syed-Abdul et al, 2019). Additionally, several studies have implemented the VR intervention in clinical settings with children and adolescent populations, but there have been fewer studies focusing on the older adult population (Skurla et al, 2021).…”
Section: R E S U M E Nmentioning
confidence: 99%